Assessment of Children's Mental Health in Irish Primary Schools - O'Farrell, Pia (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
Background: Numerous studies examine teachers' implementation of mental health interventions in schools (Franklin,et al., 2012). However, there are a paucity of studies which examine assessment of mental health in schools. Considering the percentage of their waking hours children spend in the school, and the potential role that teachers can have, research in this area is vital (Cooper & Jacobs 2011; Levitt, et al., 2007). Research aim/objectives: The two overarching questions which form this study were firstly, what are the barriers to and enablers of assessment of mental health in schools and, secondly, what is the nature and structure of anxiety in children? Methods and data sources: Stratified random sampling was used to gather data from 15 schools in the greater Dublin area. This involved 914 children (8-12 years) who completed the Revised Children's Manifest Anxiety Scale'Second Edition (RCMAS-2) and a research designed questionnaire (this questionnaire asked children whether they experience anxiety at home and at school and if so how), while 58 teachers completed a researcher designed Teacher Nomination Checklists (TNCs) and the scores on both measures (the RCMAS-2 and TNC were compared The reliability and factor structure of the RCMAS-2 were examined. Of these 58 teachers purposive sampling was used to select three schools (n=11 teachers) to participate in semi-structured interviews on assessment of mental health in schools, while a systematic review of the literature on teachers' perceptions of assessment of mental health in schools was also completed. Ethical approval was obtained. Key findings: The results of the factor structure show that different indices favour different models and that no one model provided a best fit to the data. The RCMAS-2 demonstrated good internal consistency, which was similar to the initial standardisation in the test manual. Findings which compared the RCMAS-2 to the TNCs scores indicated that teachers were generally able to identify less than half of the children who scored above 60 on the RCMAS-2. Six teacher factors (gender, age, years of experience teaching, years of experience in learning support and resource teaching, completion of training in anxiety, completion of further postgraduate qualification in working with children with BESD) and two school factors (school status and school type) were examined but none of these eight factors were found to play a role in predicting why teachers are missing children who are presenting as at risk of developing anxiety on the RCMAS-2. Findings from the research designed questionnaire completed by the children indicated that school-work and social interaction were the main source of anxiety for children, while feeling distracted was the primary consequence of anxiety for these children. Results from the systematic review and the semi-structured interviews which examined teachers' perceptions of the barriers and enablers to assessment of mental health in schools found that teachers' lack of training in assessment of mental health and `role conflict' were key barriers to assessment of mental health in schools. Educational and clinical implications of the findings for those who work with children are discussed, and suggestions for further research on the RCMAS-2 in Ireland and on assessment of mental health in schools are given.
APPROVED
Keywords: assessment mental health; anxiety; Revised Children's Manifest Anxiety Scale' Second Edition